Allyl-Isothiocyanate and Microcystin-LR Reveal the Protein Phosphatase Mediated Regulation of Metaphase-Anaphase Transition in Vicia faba - Garda, Tamás; Kónya, Zoltán; Freytag, Csongor; Erdődi, Ferenc; Gonda, Sándor; Vasas, Gábor; Szücs, Boglárka; M-Hamvas, Márta; Kiss-Szikszai, Attila; Vámosi, György; Máthé, Csaba (Frontiers in Plant Science, 2018)
Horseradish allyl isothiocyanate (AITC, a volatile oil) and cyanobacterial microcystin-LR (MCY-LR, a cyclic heptapeptide) affect eukaryotic cell cycle. MCY-LR inhibits protein phosphatases PP1 and PP2A. We aimed to reveal the mechanisms of their cellular effects in a model eukaryote, Vicia faba. We have shown for the first time that AITC had minor effects on PP1 and PP2A activities in vitro, but it inhibited significantly PP1 in vivo. The combination of 10 µM AITC with 10 µM MCY-LR induced metaphase arrest after short-term (12 h) treatments. 10 µM AITC, 0.2-10 µM MCY-LR and their combinations induced histone H3 hyperphosphorylation, associated with the regulation of metaphase-anaphase transition. This hyperphosphorylation event occurred at any treatment which led to the inhibition of PP1 activity. 10 µM AITC + 10 µM MCY-LR increased the frequency of metaphase spindle anomalies, associated with metaphase arrest. We provide new insights into the mechanisms of metaphase-anaphase transition. Metaphase arrest is induced at the concomitant hyperphosphorylation of histone H3, alteration of metaphase spindle assembly and strong inhibition of PP1+PP2A activity. Near-complete blocking of metaphase-anaphase transition by rapid protein phosphatase inhibition is shown here for the first time in plants, confirming a crucial role of serine-threonine phosphatases in this checkpoint of cell cycle regulation. Tissue-dependent differences in PP1 and PP2A activities induced by AITC and MCY-LR suggest that mainly regulatory subunits are affected. AITC is a potential tool for the study of protein phosphatase function and regulation. We raise the possibility that one of the biochemical events occurring during AITC release upon wounding is the modulation of protein phosphatase dependent signal transduction pathways during the plant defence response.